Ruminant keeping around mangrove forests in Benin (West Africa): herders’ perceptions of threats and opportunities for conservation of mangroves - Bidossessi Syntiche Chiméi Mérimée Ahouangan; Bossima Ivan Koura; Clément Sèwadé; Mireille Scholastique Toyi; Armel Dodji Paolo Lesse; Marcel Romuald Benjamin Houinato (Discover Sustainability, 2022)
Abstract In the Republic of Benin, mangroves are an essential resource for the coastal populations who use them for firewood, salt production, and ruminant feeding. However, little information exists on livestock keepers’ particular threats to mangroves. This study aims to understand the use of mangrove species by ruminant keepers to identify sustainable actions for mangroves conservation in the coastal area of Benin. Ethno-botanical and socio-economical surveys were conducted on ninety (90) ruminant farmers in fifteen (15) villages close to mangroves along the coastal belt using a semi-structured questionnaire. The herders provide their animals with different mangrove plant species for feeding and health care. Rhizophora racemosa, Avicennia africana, Paspalum vaginatum, Zanthoxylum zanthoxyloides and Blutaparon vermiculare were the primary species used for ruminants. Local communities of herders were aware of the need to restore and ensure the sustainable use of mangrove ecosystems. The main restoration and conservation strategy suggested was planting the true mangroves plant species. Others strategies were rational use of mangroves resources and avoiding burning mangroves. These strategies varied with the ethnical group of the herder and the mangrove status (degraded or restoring) in their location. The study also revealed the willingness of ruminant breeders to participate in actions to conserve mangroves. This participation in mangrove restoration was influenced by the ethnical group and age of the herder. Therefore, it is important to involve more ruminant farmers in activities and projects for mangroves restoration. Further study could evaluate whether grazing could enhance the other ecosystem services of mangroves.